2015
DOI: 10.1160/th15-04-0280
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of mean platelet volume in patients with coronary artery disease

Abstract: Large platelets with high haemostatic activity may lead to increased platelet aggregation.. Mean platelet volume (MPV), an indicator of platelet reactivity, may emerge as a prognostic marker in patients with coronary artery disease (CAD). It was the objective of this study to conduct a systematic review and meta-analysis to assess prognostic effects of MPV on cardiovascular events (CVE) in CAD patients. We searched MEDLINE and SCOPUS from inception to January 2, 2014. All studies that reported MPV and the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 67 publications
0
43
0
1
Order By: Relevance
“…The strengths of this study are the large number of patients, the well-matched controls, and consideration of comorbidities. Previous studies reported that increased MPV is associated with smoking, obesity, diabetes, coronary artery disease and medication use [26]. Although some studies showed that MPV was higher in patients with thyroid malignancies than in patients with benign thyroid disease and control subjects, these studies included small number of patients and failed to rule out the influence of comorbidities and some drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study are the large number of patients, the well-matched controls, and consideration of comorbidities. Previous studies reported that increased MPV is associated with smoking, obesity, diabetes, coronary artery disease and medication use [26]. Although some studies showed that MPV was higher in patients with thyroid malignancies than in patients with benign thyroid disease and control subjects, these studies included small number of patients and failed to rule out the influence of comorbidities and some drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence from the literature suggest that a direct correlation exists between MPV and these traditional cerebrovascular risk factors [55][56][57][58][59][60]. MPV was significantly higher (0.65 fL) in individuals with coronary artery disease and patients with high MPV had 17% higher chance of having cardiovascular events compared to patients with low MPV [61]. Another meta-analysis concluded that MPV was significantly higher in those with acute myocardial infarction than those without acute myocardial infarction [62].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies were conducted in patients with ACS. A meta-analysis [26] reported that MPV was higher in patients who developed cardiovascular events than in non-cardiovascular event patients, particularly those with MI and death. MPV may be a predictive factor of future MI or death in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%